Chemokine ligand 2: beyond chemotaxis—a multifaceted role in tumor progression - Jin, Yeying; Wang, Yixuan; Yang, Rui (Frontiers in Immunology, 2025)
Chemokine ligand 2 (CCL2) is a key regulatory molecule in the tumor microenvironment (TME) participating in the occurrence, progression, and metastasis of tumors through complex mechanisms. This paper systematically reviews the production and regulation of CCL2 in tumors and its pleiotropic effects. CCL2 can be continuously produced by tumor cells, stromal cells, and host–tumor interactions through constitutive secretion, microenvironmental stimulation response, and interaction network. Its expression is regulated by transcription factors such as Nuclear factor-kappa B (NF-κB), signal transducer and activator of transcription 3 (STAT3), and activator protein 1 (AP-1); single nucleotide polymorphisms (SNPs); and epigenetic modifications such as DNA methylation and noncoding RNA. Inflammatory factors (such as tumor necrosis factor [TNF]-α, interleukin [IL]-1β, and IL-6) and hypoxia signal in the TME further amplify CCL2 secretion through the activation of NF-κB, MAPK, and other pathways, forming a positive feedback loop. CCL2 directly promotes the proliferation, migration, and epithelial–mesenchymal transition of cancer cells by activating CCR2 receptor and its downstream PI3K/AKT, MAPK, and other signaling pathways and remodels the immunosuppressive microenvironment by recruiting tumor-associated macrophages and myeloid-derived suppressor cells. Furthermore, CCL2 drives tumor invasion and distant metastasis by inducing angiogenesis, enhancing matrix metalloproteinase activity, and promoting premetastatic niche formation. Although clinical trials targeting the CCL2–CCR2 axis have been carried out, the efficacy is limited by the redundancy of CCL2 expression and its crosstalk with other factors. Given our incomplete understanding of its mechanism, the development of combined strategies or miRNA, epigenetic intervention, and other source regulation methods is necessary. This study provides a theoretical basis for understanding the tumor regulatory network of CCL2 and the development of precise targeted therapy.